(3GdeSJYjf aj GdeaQOGJ GdWHjYjIs - (3jhfS Hf ESMGb Hf HcdGQT GdGSQGFjdj,J (B500 (3g` s
(3ChdgG (B:s
(3bGd GdeDda Gf cGf GdeJbOehf bO GdahG GhOhfhG hUfahG hGMSfhG adjS Pdc dge OhQ ef JCNQ ReGfg s
(3BNQgG (B:s
(3TMe GdSec GPG CPjH eY GdYSd hGcJMd Hg Ldj GdHUQ hbhGg s
(3Vef eLehY , JQJjHgG (B: 2s
(3CdaI dGHj LYaQ CMeO Hf GdeDJef GdeSJYjf HGddgs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs